2022
DOI: 10.32604/iasc.2022.020898
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Software Success Through Structural Equation Modeling

Abstract: Determining factors influencing the success of software projects has been the emphasis of extensive research for more than 40 years. However, the majority of research in this domain has focused on developed countries, with little attention paid to underdeveloped and developing countries. The primary objective of this article was to assess the effect of critical elements on the success of software projects in underdeveloped countries (like Pakistan), because enterprise environmental factors and staff working ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The study by Hamid et al [28] concentrated on factors that influence software project success. The SEM analysis included four constructs: planning, human resource, estimation of time, and estimation of cost.…”
Section: Discussion Of Semsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Hamid et al [28] concentrated on factors that influence software project success. The SEM analysis included four constructs: planning, human resource, estimation of time, and estimation of cost.…”
Section: Discussion Of Semsmentioning
confidence: 99%
“…The human resource factor partly reflects OrgPeople in the present study and the planning construct is probably somewhat related to our AgileChange factor. Unfortunately, Hamid et al [28] neither provided item descriptions nor their original wording, so it is difficult to determine what they covered in this factor. The overall model quality parameters were decent, and the beta coefficients were statistically different than zero.…”
Section: Discussion Of Semsmentioning
confidence: 99%
See 1 more Smart Citation
“…M. Hammid et al observed that improper planning, lacking human resource and incorrect estimation of cost and timelines have negative impact on software project success. They used hypothesis analysis in their empirical findings in which monitoring and understanding of these aspects are very essential during development [48] [51]. The main hurdles that could harm software project house's reputation can explain by Amjad et al [1] in his article.…”
Section: Project Success and Failure Factorsmentioning
confidence: 99%
“…The Devourlish is a multi-platform Apps, and capable run-on both Personal computers (PC) and Smartphones; The Google-Play and Apple-Apps Store Ecosystems (Hamid et al, 2022;Sopa et al, 2020).…”
Section: The Devourlishmentioning
confidence: 99%